Mesenchymal Stem Cell-Derived Exosomes Ameliorate Doxorubicin-Induced Cardiotoxicity - Sawdah A. Ali; Dinender K. Singla (MDPI AG, 2024)
Doxorubicin (DOX) is an incessantly used chemotherapeutic drug that can cause detrimental dose-dependent effects such as cardiotoxicity and congestive heart failure. Hence, there is a need to discover innovative therapeutic approaches to counteract DOX-induced cardiotoxicity (DIC). MSC-Exos have shown to reduce apoptosis and cardiac fibrosis and promote cardiomyocyte proliferation in myocardial infracted mice. However, the effect of MSC-Exos on ameliorating DOX-induced pyroptosis has not been investigated. In this current study, H9c2 were first exposed to DOX to stimulate pyroptosis, followed by subsequent treatment with MSC-Exos, with further analysis performed through immunocytochemistry, western blotting, and RT-PCR. Our data depicted that post-treatment with MSC-Exos significantly (p < 0.05) reduced the HMGB1/TLR4 axis, inflammasome formation (NLRP3), pyroptotic markers (caspase-1, IL-1β, and IL-18), and the pyroptotic executioner (GSDMD) in DOX-treated H9c2 cells. In conclusion, our data show that MSC-Exos attenuates inflammation-induced pyroptosis in our in vitro DIC model. Our findings indicate that MSC-Exos may serve as a promising therapeutic intervention for mitigating DIC, as they maintain the therapeutic capabilities of MSCs while circumventing the drawbacks associated with traditional stem cell therapy.